The Directive Forms of Illocutionary Act in the Transcript of Vladimir Putin’s Speech (2022) - Juliven, Azetko; Rullyanti, Merry; Putra, Dhanu Ario (Yayasan Darusssalam Bengkulu, 2021)
The directive forms of illocutionary act is a form of speech act that aims to influence the speech partner to take certain actions. This research aims to analyze the directive forms of illocutionary act contained in the transcript of Vladimir Putin’s Speech (2022). This research has 2 objectives: 1) To identify the directive forms of illocutionary act contained in the transcript of Vladimir Putin’s Speech (2022). 2) To find out the function of the directive forms of illocutionary act contained in the transcript of Vladimir Putin’s Speech (2022). This research used descriptive qualitative method and using the directive forms of illocutionary acts theory from Ibrahim (1993). The results obtained from this research found 16 the directive forms of illocutionary acts in Vladimir Putin's speech (2022) which were divided into 7 forms, namely 3 forms of asking, 3 forms of prohibiting, 3 forms of wanting, 3 forms of inviting, 2 forms of suggesting, 1 forms of requesting, and 1 forms of demanding. While the functions of the directive forms of illocutionary acts found are 7 forms which were divided into 2 functions, namely 4 competitive functions and 3 convivial functions.